Čebelar Merops apiaster - Bordjan, Dejan (Acrocephalus, 2018)
Two solitary breeding pairs observed in 2017, one of them near the village of Paunoviči in Bela krajina (SE Slovenia). This is the first breeding record for the region. The second individual was observed along the Reka river near the village of Jablanica (SW Slovenia).
Keywords: čebelar; Merops apiaster; ornitologija; ptice